Management of Neuropathic Pain Associated with Spinal Cord Injury - Hagen, Ellen M. (Pain Ther, 2015)
Spinal cord injury (SCI) is an injury to the spinal cord that leads to varying degrees of motor and/or sensory deficits and paralysis. Chronic pain of both neuropathic and nociceptive type is common and contributes to reduced quality of life. The aim of the review is to provide current clinical understanding as well as discuss and evaluate efficacy of pharmacological interventions demonstrated in the clinical studies. The review was based on literature search in PubMed and Medline with words “neuropathic pain” and “spinal cord injury”. The review included clinical studies and not experimental data nor case reports. A limited number of randomized and placebo-controlled studies concerning treatment options of neuropathic pain after SCI were identified. Amitriptyline, a tricyclic antidepressant and the antiepileptic drugs, gabapentin and pregabalin, are most studied with demonstrated efficacy, and considered to be the primary choice. Opioids have demonstrated conflicting results in the clinical studies. In addition, administration route used in the studies as well as reported side effects restrict everyday use of opioids as well as ketamine and lidocaine. Topical applications of capsaicin or lidocaine as well as intradermal injections of Botulinum toxin are new treatment modalities that are so far not studied on SCI population and need further studies. Non-pharmacological approaches may have additional effect on neuropathic pain. Management of pain should always be preceded by thorough clinical assessment of the type of pain. Patients need a follow-up to evaluate individual effect of applied measures. However, the applied management does not necessarily achieve satisfactory pain reduction. Further clinical studies are needed to evaluate the effect of both established and novel management options.